Pengaruh Model Pembelajaran TGT (Teams Games Tournament) dengan Pendekatan Deep Learning pada Pembelajaran Biologi terhadap Hasil Belajar Siswa - Rizky Rahmawati; Ali Sadikin; Raissa Mataniari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The low biology learning outcomes of students at SMA Negeri 8 Jambi City are indicated by the large number of students who have not yet achieved the Minimum Competency (MC), the lack of active involvement in learning, and the difficulty in understanding concepts in depth. This condition indicates the need for the implementation of innovative learning models to improve student learning outcomes. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model with a deep learning approach on students' biology learning outcomes. The research method used is a quasi-experimental design with a non-equivalent control group design. The research sample consisted of 70 students, namely 36 students in the experimental class using the TGT model based on deep learning, and 34 students in the control class using the Problem Based Learning (PBL) model based on deep learning. Data collection techniques were carried out through pre-tests and post-tests as well as observation sheets for learning implementation. The results showed a significant difference between the two classes with a significance value of 0.015 <0.05. The average post-test score for the experimental class (70.22) was higher than that for the control class (61.44), and the calculated effect size was 0.57, which is considered moderate. Furthermore, the N-Gain Score analysis also showed a higher increase in learning outcomes in the experimental class (0.452) than in the control class (0.376). Thus, the deep learning-based TGT learning model significantly improved students' biology learning outcomes.